Blockchain-Enabled Marketing Analytics for Enhanced Campaign Transparency - Khair, Md Abul (American Journal of Trade and Policy, 2023)
In the digital age, blockchain technology has enormous potential to transform marketing analytics and improve campaign transparency. This project aims to investigate how blockchain-enabled marketing analytics might enhance the efficacy and transparency of campaigns. The primary aims of the research were to examine the difficulties associated with conventional marketing analytics, investigate blockchain-based remedies, evaluate real-world case studies, deliberate on potential future paths and valuable suggestions, and evaluate the constraints and policy ramifications. The study's approach comprised a thorough analysis of case studies, literature, and professional comments from blockchain and marketing analytics experts. The fundamental discoveries include discovering blockchain-based solutions for conventional marketing analytics problems, presenting real-world applications through case studies, identifying future directions, and helpful adoption advice. The need for regulatory frameworks to manage data privacy issues, advance interoperability, and assist with initiatives for cooperation and education are among the policy consequences. This study sheds light on the revolutionary possibilities of blockchain-enabled marketing analytics for raising campaign transparency and spurring innovation in digital marketing.
Keywords: Blockchain; Marketing Analytics; Campaign Transparency; Digital Marketing; Data Integrity; Decentralization; Trustworthy Analytics; Distributed Ledger Technology